Sodium cantharidate promotes autophagy in breast cancer cells by inhibiting the PI3K–Akt–mTOR signaling pathway - Pang, Jin-Long; Xu, Lian-Song; Zhao, Qian; Niu, Wen-Wen; Rong, Xiang-Yu; Li, Shan-Shan; Li, Xian (Frontiers in Pharmacology, 2022)
Sodium cantharidate (SCA) is a derivative of cantharidin obtained by its reaction with alkali. Studies have shown that it inhibits the occurrence and progression of several cancers. However, therapeutic effects of SCA on breast cancer are less well studied. This study aimed to clarify the effect of SCA on breast cancer cells and its mechanism, and to provide a scientific basis for the clinical use of SCA for the treatment of breast cancer. The results of cell counting kit-8, colony formation assay, and 5-ethynyl-2'-deoxyuridine staining showed that SCA inhibited breast cancer cell proliferation. Wound-healing and transwell assays demonstrated that SCA inhibited the migration and invasion of breast cancer cells. Transmission electron microscopy revealed that SCA induced autophagy in breast cancer cells. RNA sequencing technology showed that SCA significantly regulated the phosphoinositide 3-kinase–Akt–mammalian target of rapamycin (PI3K–Akt–mTOR) pathway, which was further verified using western blotting. The inducing effect of SCA on breast cancer autophagy was reversed by the mTOR activator MHY1485. In addition, subcutaneous xenograft experiments confirmed that SCA significantly inhibited tumor growth in vivo. Hematoxylin-eosin, TdT-mediated dUTP nick-end labeling, and immunohistochemical staining indicated that SCA induced tumor cell autophagy and apoptosis in nude mice without causing organ damage. In summary, we found that SCA promoted breast cancer cell apoptosis by inhibiting the PI3K–Akt–mTOR pathway and inducing autophagy.